2017
DOI: 10.3325/cmj.2017.58.364
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ willingness to pay for cognitive pharmacist services in community pharmacies

Abstract: AimTo determine the general population willingness to pay for cognitive pharmacist service in community pharmacy, describe the behavior of participants regarding health care issues, and evaluate correlation between participants’ sociodemographic characteristics or attitudes and their willingness to pay.MethodsA questionnaire-based survey was conducted among general population visiting community pharmacies. The participants were asked about receiving cognitive pharmacist services to identify and resolve potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The WTP method is by far the most suitable method to measure the economic value of unmarketed services such as counseling in this case (Smith, 1983;Johannesson and Jonsson, 1991;O'Brien and Viramontes, 1994;O'Brien et al, 1998;Suh, 2000). This could be examined by utilizing several methods namely conjoint analysis, choice modeling, discrete choice experiment (DSE), or the most commonly used contingent valuation (CV) technique, with either revealed or stated preference approach in which patients are asked to quote an amount that they are willing to pay for a particular service (Suh, 2000;Taylor and Armour, 2002;Drummond et al, 2005;Aizuddin et al, 2014;Gupta and Çakanyıldırım, 2016;Lakić et al, 2017). Few studies have endeavored to measure the economic impact of pharmacy services through WTP as a proxy (Smith, 1983;Johannesson et al, 1993;Gafni, 1997;Suh, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The WTP method is by far the most suitable method to measure the economic value of unmarketed services such as counseling in this case (Smith, 1983;Johannesson and Jonsson, 1991;O'Brien and Viramontes, 1994;O'Brien et al, 1998;Suh, 2000). This could be examined by utilizing several methods namely conjoint analysis, choice modeling, discrete choice experiment (DSE), or the most commonly used contingent valuation (CV) technique, with either revealed or stated preference approach in which patients are asked to quote an amount that they are willing to pay for a particular service (Suh, 2000;Taylor and Armour, 2002;Drummond et al, 2005;Aizuddin et al, 2014;Gupta and Çakanyıldırım, 2016;Lakić et al, 2017). Few studies have endeavored to measure the economic impact of pharmacy services through WTP as a proxy (Smith, 1983;Johannesson et al, 1993;Gafni, 1997;Suh, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, about 60% of respondents were willing to pay for pharmacist's services aimed at reducing medication-related problems 24 . However, a lower proportion (38%) of patients were willing to pay for pharmacist cognitive services in Serbia 15 . Although pharmacist's services generally appear unnoticed in Nigerian hospitals, the high proportion of patients who are willing to pay for MERS in the present study probably indicate high patients' acceptance due to the perceived benefit of MERS.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, respondents in the present study were willing to pay less than $1 for the hospital pharmacist's services evaluated. However, previous studies that investigated the economic value of certain pharmacist's services reported that respondents were willing to pay between US$1 to US$33 15,28 . For instance, studies in the United States and Canada independently reported that patients were willing to pay about US$33 and US$25, respectively for pharmacist-provided medication management services 17,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a better market position [9], pharmaceutical care may also lead to additional profits for pharmacies. Lakic et al [23] and Jaber et al [24] showed that patients were willing to pay for pharmaceutical care services. Pharmaceutical care was also cost-effective [25,26]; hence, healthcare decision-makers might consider financial incentives for such services.…”
Section: Discussionmentioning
confidence: 99%